The Urgency of Anti-Corruption Education as a Preventive Instrument in Law Enforcement in Indonesia: A Normative Study of Article 2, Article 3, and Article 12B of the Anti-Corruption Law - Ardhian Lukman Hakim; Suyanto (JOSAR (Journal of Students Academic Research), 2026)
Corruption remains one of the structural problems that continues to pose a serious challange to the legal system i Indonesia. So Far efforts to combat corruption have largely focused on represive approach through criminal law enforcement. However, such approaches have not been fully effective  in sustainably reducing  corruption rates. Therefore, a more comprehensive approach  is needed through preventive instruments, one of which is anti-corruption education. This study aims to analyze the position of anti corruption education  as a preventive instrumentin law enforcement in Indonesia and to examine the relevance of Article 2,3  and 12 B of the Anti Corruption Law in supportig the Effort. This research employs a normative legal  research method  using a status approach and a conceptual approach. The data used consist primary and secondary legal materials which are analyzed qualitatively. The result of the study indicate that anti corruption education has a strategic position as  a preventive instrument in law enforcement as it is capable of fostering legal awarenessand individual integrity  from an early stage .Furthermore articles 2 and 3  provide a normative basis regarding forms of corruption that must be prevented while Article 12 B on Gratuities  strengthens the importance of public understanding of corruptpractice in everyday life. Thus the integration of penal and non penal aproavhes through anti corruption education is essential in creating a more effective and sustainable lw enforcement in Indonesia.